2014
DOI: 10.1186/2049-6958-9-60
|View full text |Cite
|
Sign up to set email alerts
|

COPD: adherence to therapy

Abstract: Adherence to medical therapies is a growing issue, so much so that the World Health Organization defined it as “a new pharmacological problem”. The main factors affecting compliance are: frequency of administration, rapid onset of action, role of device. The most severe consequence of non-adherence is the increased risk of poor clinical outcome, associated with worsening of the quality of life and increase in health-care expenditure. It appears crucial to identify those COPD patients who are “poorly or not at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 33 publications
4
62
1
6
Order By: Relevance
“…7,11,12 Other factors that are also thought to play a role in medication adherence include frequency of administration, rapid onset of action and ease of use of inhaler device. 21 We found that patients who reported high adherence were significantly older than the cohort who reported suboptimal adherence (73 vs. 68, p ¼ 0.001), which is consistent with the findings of previous studies. 6,7,22 It has been hypothesized that this may be due to more organized behaviour in old age, which can facilitate better adherence to medications.…”
Section: Discussionsupporting
confidence: 92%
“…7,11,12 Other factors that are also thought to play a role in medication adherence include frequency of administration, rapid onset of action and ease of use of inhaler device. 21 We found that patients who reported high adherence were significantly older than the cohort who reported suboptimal adherence (73 vs. 68, p ¼ 0.001), which is consistent with the findings of previous studies. 6,7,22 It has been hypothesized that this may be due to more organized behaviour in old age, which can facilitate better adherence to medications.…”
Section: Discussionsupporting
confidence: 92%
“…Responses are scored using the Morisky scale to give a general indicator of risk 11. See Sanduzzi et al11 for the complete questionnaires.aQuestion relates to the patient’s health condition, and economic and family situations. Data from Sanduzzi et al11…”
Section: Figurementioning
confidence: 99%
“…Incorrect use of inhaler devices is common – real-world studies estimate that up to 94% of patients do not use their inhalers properly 6,8,9. This can lead to inadequate drug dosing, which, in turn, contributes to a worsening of quality of life and suboptimal disease control 811…”
Section: Introductionmentioning
confidence: 99%
“…This was also observed by Izquierdo et al28 in another population-based study in Spain in which they observed a high rate of compliance with treatment with LAMAs and no differences between the different products. In any case, patients initiating treatment with ACL or TIO in our study differed in variables that have been shown to have an impact on treatment adherence, for example, severity of the disease, age, and number of concomitant medications 20,21,29. Consequently, these important differences did not allow us to formally compare the rates of persistence between both drugs.…”
Section: Discussionmentioning
confidence: 92%